The Role of Affinity Group in Improving Welfare in Maqashid Shari’ah Perspective - Imari, Iqbal; Armina, Sheema Haseena; Waskito, M. Agus (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2024)
The purpose of this study is to clarify the role of Independent Women's Affinity Groups and to examine the maqashid shari'ah (Hifdzul Maal) in their operations to assist the Ngunut Village. This research is primarily qualitative. Collection of data methods include observation, interviews, and documentation in order to acquire accurate, objective, and concrete results. Simply describe the questionnaire used during data collecting to strengthen qualitative data. The observation and interview results suggest that the welfare situation of the communities in the hamlet of Ngunut is typically positive and improving. Proven through the use of natural resources by productive organizations, human resources through recitation, and the provision of training all contribute to the growth of knowledge and skills. Social capital, which includes capital fertilization for savings and loans, as well as collaboration among groups, governments, and private individuals, all contribute to the development of social skills. The questionnaire findings show how many members benefit from the Independent Women's Affinity Groups, including greater income. While, according to the Maqashid Shari'ah (Hifdzul Maal) evaluation, the Independent Women's Affinity Groups are performing successfully and in accordance with Islamic Shari'ah. According to DSN-MUI Fatwa Nomor 11/DSN-MUI/IV/2000, Independent Women's Affinity Groups' contracts do not violate the applicable requirements. Members will have even greater convenience in enhancing their welfare.